The Future of Offshore Financial Centres. A Case Study of Bermuda - Forbes, Anna C. (2009)
The future of offshore financial centres has been a major topic of legal and political debate in recent years. Whilst offshore centres around the globe have reaped substantial rewards in the past two decades, it is debateable whether this can and should be sustained. As one of the most prosperous offshore financial centres, the study of Bermuda can be interpreted and applied to other offshore financial centres in the Caribbean. The analysis of international businesses and their employees is the central concept in this study in order to analyse the future of international business, and in particular the financial industry. A review of international expansion into foreign markets and the external factors associated with this will be analysed, followed by an analysis of ten interview subjects that have been chosen as representatives of the banking, insurance, and accounting industries on the island. The opinions of both expatriate and Bermudian citizens will be the main focus of my thesis due to the fact that the future of international business in Bermuda is highly dependent on skilled professionals remaining on the island. Their interpretation of the future is therefore the most important element.